ANALISIS PIOTROSKI F-SCORE PADA SAHAM JAKARTA ISLAMIC INDEX 70 PERIODE TAHUN 2019-2021 - Ahmad Sandiffu’ad; Safwira Guna Putra (Universitas Islam Negeri Mataram, 2022)
In investing, one of the analyzes that must be carried out by investors is to carry out fundamental analysis. One method that can be used to view company performance, especially the information contained in financial reports, is the Piotroski F-Score. This study relies on secondary data in the form of published company financial reports, then analyzed using a quantitative approach to measure the financial performance of each company. Data analysis was carried out by calculating the nine Piotroski F-Score assessment variables, then giving a score to each of these criteria. The sampling technique used purposive sampling where only 55 companies were included in the sample criteria. The results showed that the use of the Piotroski F-Score was able to show Islamic stocks with good performance as seen from the high Piotroski F-Score values ??for companies included in the Jakarta Islamic Index 70 for the 2019-2021 period. Of the 55 samples analyzed, there were 34 stocks that had scores in the range of 0-3 which were categorized as companies with low performance, investors were recommended to avoid or not invest in these companies. And there are 21 companies that have a score of 4? ???????????? ? 7 which are categorized as companies with medium performance which are eligible for investment.In investing, one of the analyzes that must be carried out by investors is to carry out fundamental analysis. One method that can be used to view company performance, especially the information contained in financial reports, is the Piotroski F-Score. This study relies on secondary data in the form of published company financial reports, then analyzed using a quantitative approach to measure the financial performance of each company. Data analysis was carried out by calculating the nine Piotroski F-Score assessment variables, then giving a score to each of these criteria. The sampling technique used purposive sampling where only 55 companies were included in the sample criteria. The results showed that the use of the Piotroski F-Score was able to show Islamic stocks with good performance as seen from the high Piotroski F-Score values ??for companies included in the Jakarta Islamic Index 70 for the 2019-2021 period. Of the 55 samples analyzed, there were 34 stocks that had scores in the range of 0-3 which were categorized as companies with low performance, investors were recommended to avoid or not invest in these companies. And there are 21 companies that have a score of 4? ???????????? ? 7 which are categorized as companies with medium which are eligible for investment.